Collectivity and the Boundary Subject: Between Collective and Individual Subjectivity in Psychology - Pasgaard, Jeppe (International Review of Theoretical Psychologies, 2026)
Across the field of educational and social psychology, the term ‘collective(s)’ has proven to be an increasingly predominating concept in analyzing the preconditions of mental health and wellbeing. However, with the prevalence of self-help practices and literature, we are often left with an unsatisfactory negativity of collectivity, and the general question of whether or how to conceptualize activities of the solitary individual as a social practice. When psychologies deal with collectives rather than collectivity, the collective status of individual subjectivity often remains unaddressed, and this negativity forms the outset for this paper. The paper thus explores the implications of leaving individual subjectivity in the shadows of favoring collectives and collective subjectivity, thus questioning whether the subject as an individual unit is truly non-collective, or if we can articulate collectivity and subjectivity in a way that bridges this gap. To explore this issue, the paper rearticulates the notion of collectivity through dialogical engagements with different receptions of the ‘collective condition’ of subjectivity, i.e., as ideology (Zizek), boundary objectivity (Nissen), and hereditary sin (Kierkegaard). Concepts of uncollectivity and boundary subjectivity are presented as means to overcome the psychological implications when collectivity is only grasped through the external contradiction of individual and collective subjectivity.